2020
DOI: 10.1080/23802359.2020.1715856
|View full text |Cite
|
Sign up to set email alerts
|

The complete mitochondrial genome of a Green macroalgae species: Ulva meridionalis (Ulvales: Ulvaceae)

Abstract: Ulva meridionalis, a green macroalgae, is one of the causal species for green tides in Japan and spread into the coast of China. During this research, we sequenced the complete mitochondrial genome of U. meridionalis. The mitogenome is 62,887 bp in length, including 28 encoding genes and 29 tRNA genes. Compared with the Ulva species from mitogenome, the gene order and organization of this mitogenome are similar to most of other determined Ulva mitogenomes, with the nucleotide base composition of A 33.6%, T 32.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…(MN853878) to form an independent subclade with high support value (100%) (Figure 7). An incomplete mitogenome (MN861072) from one Ulva sample designated as U. meridionalis previously has been sequenced (Kang et al, 2020), which lacks the region from rps10 to cox1. However, our result of phylogenomic analysis showed that this Ulva sample was closely related to U. flexuosa (Figure 7).…”
Section: Phylogenetic and Phylogenomic Analysesmentioning
confidence: 99%
“…(MN853878) to form an independent subclade with high support value (100%) (Figure 7). An incomplete mitogenome (MN861072) from one Ulva sample designated as U. meridionalis previously has been sequenced (Kang et al, 2020), which lacks the region from rps10 to cox1. However, our result of phylogenomic analysis showed that this Ulva sample was closely related to U. flexuosa (Figure 7).…”
Section: Phylogenetic and Phylogenomic Analysesmentioning
confidence: 99%
“…Green tides, which occur widely in many coastal areas, are caused primarily by flotation, accumulation, and excessive proliferation of green macroalgae, especially the members of the genus Ulva [1][2][3]. China has the high frequency outbreak of the green tide [4][5][6][7][8][9][10]. Especially, the world's largest green tide events, have occurred annually from 2007 to 2020 along the coast of the Yellow Sea, China, seriously affecting marine environments and ecological services functions [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…China has the high-frequency outbreak of the green tides (Smetacek and Zingone 2013;Hu et al 2014;Zhang et al 2014;Zhang et al 2015;Cui et al 2019;Kang et al 2020;Xiao et al 2020). The formation of the green tide in the Southern Yellow Sea of China is complicated.…”
mentioning
confidence: 99%